Penegakan Hukum Terhadap Tambak Udang Ilegal di Taman Nasional Karimunjawa: Ancaman Pencemaran dan Kerusakan Terumbu Karang - Ayu Sekarini; Briliant Fabobya; Syailendra Elang Swastika; Putri Febri Heirani (CV. ITTC INDONESIA, 2026)
This study analyzes law enforcement against illegal shrimp ponds in Karimunjawa National Park in the context of the threat of pollution and coral reef damage. Using a normative‑legal method with a statutory and literature‑study approach, the research shows that intensive shrimp pond activities in conservation areas violate provisions of Law No. 5 of 1990 on the Conservation of Natural Resources and Ecosystems, as well as other environmental regulations. The environmental impacts include a decline in water quality, sedimentation covering coral reefs, the emergence of algal overgrowth, and a reduction in marine biodiversity. The study also identifies gaps in law enforcement, such as suboptimal inter‑sectoral collaboration, limited human and institutional resources, and the absence of specific policies regulating shrimp ponds in conservation areas. The findings are expected to serve as a basis for strengthening policy and law‑enforcement strategies that are more preventive and repressive toward illegal shrimp ponds in marine conservation areas.